Prospects of Blockchain Technology in China’s Industrial Hemp Industry - Haolu Liu; Bin Zhang; Jicheng Huang; Kunpeng Tian; Cheng Shen (Journal of Natural Fibers, 2023)
Industrial hemp is an important cash crop in China and has a very important role to play in increasing farmers’ income and eliminating poverty. However, drug loss risks, policy risks and regulatory challenges in the industrial hemp supply chain plague the healthy development of the industrial hemp industry. In order to address the problems in the industrial hemp industry, this paper described the problems in financing, traceability, and regulation, which are typical supply chain problems, by analyzing the industry of industrial hemp in China. Through a literature review, this paper reviewed the research results of blockchain technology in the agricultural supply chain, and analyzed the feasibility of blockchain technology to solve the financing problem of industrial hemp industry in combination with Chinese agricultural production and management modes, and analyzed the feasibility of blockchain technology to solve the traceability and supervision problems of industrial hemp industry in combination with Chinese anti-drug policies. Finally, based on the feasibility analysis, the idea of building a consortium blockchain consisting of market entities, financial institutions and drug-fighting agencies in the industrial hemp industry was proposed to solve the problems existing in the industrial hemp industry.